Treatment of sleep apnoea syndrome decreases cognitive decline in patients with Alzheimer's disease. Issue 12 (14th May 2014) - Troussière, Anne-Cécile; Charley, Christelle Monaca; Salleron, Julia; Richard, Florence; Delbeuck, Xavier; Derambure, Philippe; Pasquier, Florence; Bombois, Stéphanie
Abstract : Background: It is essential to detect and then treat factors that aggravate Alzheimer's disease (AD). Here, we sought to determine whether or not continuous positive airway pressure (CPAP) therapy for sleep apnoea syndrome (SAS) slows the rate of cognitive decline in mild-to-moderate AD patients. Methods: Between January 2003 and June 2011, we included consecutive, mild-to-moderate AD patients (a Mini Mental State Examination (MMSE) score at inclusion ≥15) with severe SAS as determined by video-polysomnography (an apnoea-hypopnoea index ≥30). In this single-blind, proof-of-concept trial, we analysed the mean decline in the annual MMSE score (the main outcome measure) according to whether or not the patients had received CPAP therapy. The decline was computed for each patient and for the first 3 years of follow-up. Results: Of the 23 included patients, 14 underwent CPAP treatment. The CPAP and non-CPAP groups did not differ significantly in terms of their demographic characteristics or MMSE score at baseline. The median annual MMSE decline was significantly slower in the CPAP group (−0.7 (−1.7; +0.8)) than in the non-CPAP group (−2.2 (−3.3; −1.9); p=0.013). Conclusions: In this pilot study, CPAP treatment of severe SAS in mild-to-moderate AD patients was associated with significantly slower cognitive decline over a three-year follow-up period. Our results emphasise the importance of detecting and treating SAS in this population.